2021
DOI: 10.1101/2021.11.22.469156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simultaneous assessment of eight phosphorylated STAT residues in T-cells by flow cytometry.

Abstract: Signal transducer and activator of transcription (STAT) proteins are a family of transcription factors controlling functions in immune responses and other cell types. Given their importance, we developed a flow cytometry panel to assess eight phosphorylated STAT residues in human T-cells, including six tyrosine residues across six STAT proteins (STAT1, STAT2, STAT3, STAT4, STAT5a, STAT6) and additional serine residues on STAT1 and STAT3. We applied this protocol to test the in vitro induction of pSTATs in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Data was acquired on an Attune NxT flow cytometer (Thermo Fisher, Waltham, Massachusetts, USA). For pSTAT evaluation, cells were fixed and stained per Monk et al 11 Antibodies used are reported in online supplemental table 2. Data were acquired on a BD FACSymphony flow cytometer (BD Biosciences, Franklin Lakes, New Jersey, USA).…”
Section: Correlative Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data was acquired on an Attune NxT flow cytometer (Thermo Fisher, Waltham, Massachusetts, USA). For pSTAT evaluation, cells were fixed and stained per Monk et al 11 Antibodies used are reported in online supplemental table 2. Data were acquired on a BD FACSymphony flow cytometer (BD Biosciences, Franklin Lakes, New Jersey, USA).…”
Section: Correlative Studiesmentioning
confidence: 99%
“…10 In this study, we used an expanded flow cytometry panel that was optimized to investigate seven additional pSTAT residues as additional exploratory biomarkers. 11 Paired baseline and on-treatment (week 10 or 13) patient PBMC samples were evaluated by intracellular flow cytometry for expression of pSTATs.…”
Section: Immune Correlatesmentioning
confidence: 99%